Cancer Diagnoses Following Abnormal Noninvasive Prenatal Testing: A Case Series, Literature Review, and Proposed Management Model. (10th June 2021) - Dow, Eryn; Freimund, Alison; Smith, Kortnye; Hicks, Rodney J.; Jurcevic, Peter; Shackleton, Mark; James, Paul A.; Fellowes, Andrew; Delatycki, Martin B.; Fawcett, Susan; Flowers, Nicola; Pertile, Mark D.; et al.
Abstract : Noninvasive prenatal testing (NIPT) is a screening test for fetal chromosomal aneuploidy using cell-free DNA derived from maternal blood. It has been rapidly accepted into obstetric practice because of its application from 10-weeks' gestation, and its high sensitivity and specificity. NIPT results can be influenced by several factors including placental or maternal mosaicism and co-twin demise; cell-free DNA from a maternal origin can also complicate interpretation, with evidence that NIPT can detect previously unsuspected malignancies. This study aimed to develop management guidelines for women with NIPT results suspicious of maternal malignancy. The Peter MacCallum Cancer Center's experience of seven cases where abnormal NIPT results led to investigation for maternal malignancy between 2016 and 2019 were reviewed, along with the published literature. Six of the seven women (86%) referred for investigation were diagnosed with advanced malignancies, including colorectal cancer, breast cancer, melanoma, and Hodgkin lymphoma. Based on our single-center experience, as well as the available literature, guidelines for the investigation of women with NIPT results suspicious of malignancy are proposed, including utilization of fluorodeoxyglucose positron emission tomography-computed tomography, which had a high concordance with other investigations and diagnoses. These guidelines include maternal and fetal investigations, as well as consideration of the complex medical, psychologic, social, and ethical needs of these patients and their families.